EFFECT OF LOURO-PARDO AND IT IS FERTILIZATION ON THE ACCUMULATION OF CARBON IN THE LITTERFALL AND BIOMASS OF ARUANA-GRASS IN A SILVOPASTORAL SYSTEM - Brun, Eleandro José; Viana, Carla Marins Santos Santana; Dourado, Marcela Guedes; Moreira, Flavia; Perez, Julio Cesar Farias; Casali, Carlos Alberto (Floresta, 2023)
Were evaluated the litterfall/carbon accumulation of louro-pardo as a function of different fertilization doses and the influence of the tree component on the biomass/carbon accumulation of aruana grass in a silvopastoral system in southwestern Paraná, Brazil. Samples were collected in the middle of the row (MR), in the crown projection (CP), and the midpoint between two rows (MR). Four mineral fertilization treatments applied to tree species were also compared: T0: without fertilization, T1: NPK (33-22-9), T2: NPK (66-44-18), and T3: NPK (99-66-27). The experimental design in randomized blocks was bifactorial with three positions x four doses, totaling 12 treatments with three replications, reaching 36 samples per component. Litterfall accumulation did not show significant differences between fertilizer doses and sampling positions, with a general average of 3846.8 kg ha-1. There was also no significant difference in the accumulation of aruana grass biomass between the different positions and doses, with a general average of 3479.8 kg ha-1. About to the accumulated organic carbon, there was no significant difference between the sampling positions and fertilization doses in the louro-pardo litter and the aruana grass biomass, with an average of 1791.3 kg ha-1 of carbon for the louro-pardo and 1653.1 kg ha-1 for aruana grass. The fertilization doses also did not significantly influence the carbon content of the litter of louro-pardo, which presented a general average of 1797.2 kg ha-1. In general, the fertilization of louro-pardo did not influence the amount of carbon in the litterfall, nor the amount of biomass of the aruana grass, and there was no indication for fertilization for this study.